2013
DOI: 10.2217/fmb.13.94
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Adherent–Invasive Escherichia Coli

Abstract: The etiology of Crohn's disease (CD) is complex and involves both host susceptibility factors (i.e., the presence of particular genetic alleles) and environmental factors, including bacteria. In this regard, adherent-invasive Escherichia coli (AIEC), have recently emerged as an exciting potential etiological agent of CD. AIEC are distinguished from commensal strains of E. coli through their ability to adhere to and invade epithelial cells and replicate in macrophages. Recent molecular analyses have identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 114 publications
0
22
0
1
Order By: Relevance
“…This process prevents the immune system from activating a proinflammatory response against commensal bacteria, while still maintaining the ability to protect against pathogens. When intestinal inflammation occurs, the mucosal barrier is interrupted and the specific epithelial receptors are expressed abnormally; a consequence of this is a greater intestinal permeability and susceptibility to the pathogenesis of AIEC (Antoni, Nuding, Wehkamp, & Stange, 2014;Benjamin, Makharia, Ahuja, Kalaivani, & Joshi, 2008;Sasaki et al, 2007;Smith, Thompson, O'Driscoll, & Clarke, 2013;Wine, Ossa, Gray-Owen, & Sherman, 2010). In the first moments of interaction, the ability of adhesion and invasion is given by flagella, Type 1 fimbria, outer membrane proteins (OmpCs) and…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…This process prevents the immune system from activating a proinflammatory response against commensal bacteria, while still maintaining the ability to protect against pathogens. When intestinal inflammation occurs, the mucosal barrier is interrupted and the specific epithelial receptors are expressed abnormally; a consequence of this is a greater intestinal permeability and susceptibility to the pathogenesis of AIEC (Antoni, Nuding, Wehkamp, & Stange, 2014;Benjamin, Makharia, Ahuja, Kalaivani, & Joshi, 2008;Sasaki et al, 2007;Smith, Thompson, O'Driscoll, & Clarke, 2013;Wine, Ossa, Gray-Owen, & Sherman, 2010). In the first moments of interaction, the ability of adhesion and invasion is given by flagella, Type 1 fimbria, outer membrane proteins (OmpCs) and…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Bacterial colonisation of the mucus layer or the sub-mucus niche is rare in the healthy colon but much commoner in IBD, particularly CD, where colonisation of the mucosa is also found in the terminal ileum. The most consistent abnormality is an increase of mucosa-associated Escherichia coli in CD patients [16]. The recent paediatric CD microbiota study also showed an increase in mucosa-associated species of Fusobacterium , Haemophilus and Veillonella [15].…”
Section: Microbiota-host Interactions In Ibd Pathogenesismentioning
confidence: 99%
“…Among the latter, a particular attention has been focused on adherent-invasive E. coli (AIEC), a group featured by their ability to adhere and invade intestinal epithelial cells and survive within mature phagolysosomes of macrophages [21][22][23][24]. These strains are more abundant in CD patients [19,25,26] and are thought to have a role in the early stages of disease onset [27,28]. Recently, defects in autophagy have been related to an increased persistence of AIEC inside macrophages [29,30].…”
Section: Introductionmentioning
confidence: 99%